2007
DOI: 10.1007/s00442-007-0772-5
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and lifetime fecundity in new versus old populations of the Glanville fritillary butterfly

Abstract: Life history theory often assumes a trade-off between dispersal and reproduction, and such a trade-off is commonly observed in wing-dimorphic insects. The results are less consistent for wing-monomorphic species, for which it is more difficult to assess dispersal capacity and rate. Three replicate experiments were carried out in consecutive years on the Glanville fritillary butterfly in a large outdoor population cage to study the relationship between lifetime egg production and mobility. The experimental mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
87
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(97 citation statements)
references
References 37 publications
9
87
1
Order By: Relevance
“…Previous studies on the Glanville fritillary (16,35,36) and other species (37,38) have demonstrated that colonizations select for more dispersive individuals than the average individual in the metapopulation. In the Glanville fritillary, female butterflies from newly established local populations (39,40) and from highly fragmented landscapes (28) have a higher flight metabolic rate than those from old local populations and from continuous landscapes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies on the Glanville fritillary (16,35,36) and other species (37,38) have demonstrated that colonizations select for more dispersive individuals than the average individual in the metapopulation. In the Glanville fritillary, female butterflies from newly established local populations (39,40) and from highly fragmented landscapes (28) have a higher flight metabolic rate than those from old local populations and from continuous landscapes.…”
Section: Discussionmentioning
confidence: 94%
“…Importantly, allele frequency changes in the 24-y-old introduced Sottunga metapopulation have been significantly smaller than in the SW Finnish populations, which have had on average 80 y to diverge ( Fig. 3; (16,35,36). To test this possibility, we calculated the difference in allele frequencies of outlier loci in newly colonized versus old local populations in contemporary Åland samples and correlated this difference with changes in allele frequencies in the samples from Sottunga and SW Finland in relation to the pooled sample from old large populations in the contemporary Åland metapopulation.…”
Section: Significancementioning
confidence: 96%
“…Indeed, the decline in intrinsic growth occurred despite faster development times and higher egg survival and was therefore most likely driven by strong reductions in fecundity. However, while some studies suggest that fecundity trades off with dispersal (e.g., Zera and Denno 1997;Hughes et al 2003), others have failed to detect this or even found a positive correlation (e.g., Saastamoinen 2007;Therry et al 2015). Furthermore, diapause incidence has been shown not to constrain changes in fecundity in T. urticae (Ito 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, under certain conditions highly dispersive individuals may have reduced lifetime reproductive success and/or life expectancy (Hanski and Saccheri, 2006). Previous studies have shown that fitness benefits of being dispersive or sedentary in the Glanville fritillary are highly dependent upon the spatial configuration of populations and habitat patches Saastamoinen, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is much variation in the flight capacity among individuals (Saastamoinen, 2007b), and in particular Hanski et al (2002Hanski et al ( , 2004 have shown that females originating from newly-established isolated populations are more dispersive in the field than those originating from old populations (based on a common garden mark-release-recapture experiment in the field). Comparable conclusions were drawn from a theoretical model and from physiological studies on the [ATP]/…”
Section: Introductionmentioning
confidence: 99%